Improvement of the filling and plasticization processes of forming multifunctional leather materials - Danylkovych, Anatoliy; Mokrousova, Olena; Zhigotsky, Alexander (Eastern-European Journal of Enterprise Technologies, 2016)
The study concerns the filling and plasticizing processes in the final stages of forming multifunctional leathers from various raw materials on the basis of using new composite systems. The structure of a tannin-containing composition was found to affect the process of its diffusion throughout the structure of the topographic areas of the semifinished chrome-tanned product. In particular, we have determined that the depth of diffusion of the filling composition in loose areas was close to 100 % with a 5 % use of the mass of the intermediate product; in dense areas even with a bigger use of the mass, it was only 80 % of the thickness of the intermediate product. The structure of the filling and plasticizing composition was developed to form various leathers from hides of cattle and sheep. A protein hydrolysate and a highly dispersive modified aluminosilicate have proved to influence the process of forming and the physicochemical properties of semifinished leathers. If the filling and plasticizing composition contains optimal amounts of montmorillonite and protein hydrolysate at 4–2 % of the semifinished leather mass, the obtained leather materials have respective tensile strengths of sheepskin and bovine hides of 15–16 MPa and 20–22 MPa, and their stiffness is 15–16 and 21-22 SN. The use of montmorillonite in the filling and plasticizing compositions in processing semifinished chrome-tanned products proved to ensure stability of the dispersed structure in further processing and its mobility in the cyclic deformation of the products. The complex study of the process of filling and plasticizing semifinished chrome-tanned products was the basis for developing effective technologies to produce elastic materials for footwear leather uppers and apparel and haberdashery articles with the necessary physical and mechanical properties as well as bigger volume and area outputs by 270–310 сm3/100 g of protein substance and by 5–6 %, respectively, in comparison with the outputs of the industrial technology.